EFFECT OF L-ARGININE THERAPY ON PLASMA NO2 AND NO3 LEVELS, AND BLOOD PRESSURE IN UREMIC RABBITS - Hanif, Mohammad; Karira, Khemomal A.; Iltaf, Muhammad; Rani, Mona; Khan, Nusratullah; Kumar, Haresh; Shaheena, Shaheena; Wahab, Abdul (Journal of Ayub Medical College Abbottabad, 2011)
Background: Normal kidney function is regulated by Nitric oxide (NO) and Superoxide (O2-) in the body, and consequently controls blood pressure. Nitric Oxide promotes natriuresis and diuresis, and therefore results in reduction of blood pressure. The objective of this study was to determine the effect of L-arginine supplementation on blood pressure, urinary protein, nitrite and nitrate in addition to blood urea, serum creatinine and creatinine clearance in uremic rabbits. Methods: This study was carried out in the Department of Biochemistry Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi. A total of 48 rabbits were included in the study. Twenty-four of the rabbits on surgical intervention were prepared as uremic and so became hypertensive as well. Two groups were uremic, one group was given L-arginine and the other was remained untreated. Systolic and diastolic blood pressure was measured on week 0, week 2, week 4, and week 6, while blood and urine was collected on week 0 and week 6. Results: On supplementation with L-arginine to uremic rabbits systolic and diastolic blood pressures were decreased significantly. Nitrite/nitrate and urinary protein were corrected to some extent while blood urea and serum creatinine were unaffected. Conclusion: L-arginine has a beneficial role as blood pressure lowering agent in uremic rabbits. It corrects NO2/NO3 plasma level and proteinuria which is indicator of renal failure. Keywords: Renal failure, uremia, L-arginine, hypertention, NO2/NO3